2018
DOI: 10.4103/1673-5374.232481
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel animal model for sciatic nerve repair with an adipose-derived stem cell loaded fibrin conduit

Abstract: Despite the regenerative capabilities of peripheral nerves, severe injuries or neuronal trauma of critical size impose immense hurdles for proper restoration of neuro-muscular circuitry. Autologous nerve grafts improve re-establishment of connectivity, but also comprise substantial donor site morbidity. We developed a rat model which allows the testing of different cell applications, i.e., mesenchymal stem cells, to improve nerve regeneration in vivo. To mimic inaccurate alignment of autologous nerve grafts wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…When co-cultured with motor neuron-like cells or dorsal root ganglion (DRG) sensory neurons, ASC enhanced the neurite number and outgrowth length [ 21 , 22 , 23 ]. In line with these findings, several animal studies reported enhanced axonal regeneration and sensory-motor nerve conduction, when ASC were transplanted in polymeric nerve conduits (NC) or fibrin-hydrogel nerve conduits (FNC) [ 24 , 25 , 26 ]. Improved axonal growth and elongation was found in the FNC loaded with ASC in comparison to empty FNC [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…When co-cultured with motor neuron-like cells or dorsal root ganglion (DRG) sensory neurons, ASC enhanced the neurite number and outgrowth length [ 21 , 22 , 23 ]. In line with these findings, several animal studies reported enhanced axonal regeneration and sensory-motor nerve conduction, when ASC were transplanted in polymeric nerve conduits (NC) or fibrin-hydrogel nerve conduits (FNC) [ 24 , 25 , 26 ]. Improved axonal growth and elongation was found in the FNC loaded with ASC in comparison to empty FNC [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 78%
“…However, an optimal delivery route for ASC still remains to be established in the context of peripheral nerve reconstruction. Various studies involving ASC therapy employed different cell delivery routes, i.e., injection into the lumen, dispersion within the fibrin conduit wall, dispersion within the lumen of fibrin matrix and coating on the luminal surface [ 7 , 22 , 26 , 27 , 29 , 30 ]. However, the therapeutic efficacy of the cells was scarcely correlated with delivery routes and carrier matrix in the context of nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Additional techniques for enhancing axons regeneration through long allografts grafts include filling them with platelet-rich plasma (PRP) [140], autologous Schwann cells [141,142], adipose-derived mesenchymal stem cells (ADSCs), or primary Schwann cell-like differentiated bone marrow-derived mesenchymal stem cells (DMSCs) [142][143][144][145]. These cells induce enhanced axon regeneration by releasing neurotrophic factors [146,147].…”
Section: Enhancing the Regeneration-promoting Capacity Of Allograftsmentioning
confidence: 99%
“…Axon regeneration is extensive through conduits composed of fibrin [145,153], hydrogel tubes [154], alginate/chitosan polyelectrolyte [155][156][157], poly epsilon-caprolactone [158,159], polyglycolic acid [160], poly(lactic-co-glycolic acid) or silk-based [161][162][163][164]. Conduits composed of decellularized human umbilical artery [165] and muscles [166] are also effective in promoting axon regeneration across nerve gaps.…”
Section: Conduit Compositionmentioning
confidence: 99%
See 1 more Smart Citation